Secondary antibody deficiencies. Issue 6 (December 2015) - Dhalla, Fatima; Misbah, Siraj A.
Abstract : Purpose of review: Antibody deficiency can occur in the context of primary immune deficiency due to inherited genetic defects or secondary to a variety of causes. This review aims to summarize current data concerning the causes of secondary antibody deficiency and where possible evidence regarding the use of prophylactic replacement immunoglobulin. Recent findings: Advances in immune-mediated therapies ranging from monoclonal antibodies to novel B-cell-targeted therapeutics are responsible for an expansion in the possible iatrogenic causes of antibody deficiency. Summary: Causes of secondary antibody deficiency include B-cell lymphoproliferative disease, notably chronic lymphocytic leukaemia and multiple myeloma, protein losing states, disorders of lymphatic circulation, increased immunoglobulin catabolism and a growing number of therapeutic agents. At-risk patients should be closely monitored for the development of hypogammaglobulinaemia, B-cell function should be defined where appropriate with specific antibody responses to immunization antigens and where there is a significant burden of infections patients should be treated with prophylactic antibiotics and/or replacement immunoglobulin.